КУЛТУРОЛОШКИ ИНТЕРПРЕТАЦИИ НА МЕТАФОРАТА ВАМПИРИЗАМ НИЗ ДИСКУРСОТ НА СОВРЕМЕНАТА БАЛКАНСКА КНИЖЕВНОСТ (Philological Studies, 2019)
The vampire, as a cultural category, symbolizes the cyclical transformation of survival amidst living and non-living surroundings. Due to its continuous transformational powers, this figure needs to be analyzed within the parameters of global cultural memory. This paper focuses on the mythical framework of the vampire figure, particularly within contemporary literary discourse. This paper ties to examine the presence of this mythical figure in the literary memory of contemporary Balkan literatures, by taking a closer look at The Legions of St. Adofonis by Macedonian writer Slavko Janevski, How to Kill a Vampire by Serbian writer Borislav Pekić, and The Vampire by Croatian writer Boris Perić. Hence, the chronology of the Balkans seems most desirable for the overflow of the vampire’s mythical attributes, without and beyond various cultural segments. This figure has thus been situated at the center of contemporary literature, and contemporary processes such as postcolonial criticism, globalism, multiculturalism, i.e., the meaning of the vampire rises beyond the trivial.
Keywords: vampire, myth, metaphor, Balkan, Slavko Janevski, Borislav Pekić, Boris Perić, society, culture, folklore, ideology, soul, power, the Other, Otherness